„Ökologische Kultur“, „Umweltrationalität“ und „Umweltethik“ - Leff, Enrique (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2000)
Considering the ecological crisis a new “ecological culture” is necessary. This would include a new eco-technological paradigm of production as well as a new “environmental ethics”. But such an environmental ethics may not be defined in narrow sense, the basic needs, the traditions, and the quality of life have to be taken into consideration. After all, such a framwork is not compatible with the logic of capitalist production.